Pengaruh Pemahaman Eskatologi Ditinjau dari 1 Tesalonika 4:13 – 5:11 dengan Perilaku dan Pertumbuhan Iman Jemaat di GKLI Sihabonghabong - Melina Agustina Sipahutar (EXOUSIA : Jurnal Pendidikan Agama Kristen, 2022)
The congregation's doubts about the Lord's day which will surely come, are a matter that needs to be considered, this condition of doubt greatly affects the behavior of the congregation to be serious or not in living their faith, their clear understanding of the coming of the Lord's day also affects how faith growth and the quality in the midst of his life as a believer and as a people or congregation of God's Church. When the Lord Jesus was taken up to heaven, several pairs of eyes witnessed. At that time there was a promise revealed through the angel; “This Lord Jesus, who was taken up into heaven from you, will come again in the same way, as you saw Him go into heaven” (Acts 1:11). But none of those words contain a definite meaning of time/date. Jesus Himself, when He served in the midst of this world, He promised that there would be a time when the Son of man would return with all glory and power. Yet even there Jesus said; “But as to that day or hour no one knows, neither angels in heaven nor children, only the father in heaven” (Mark 13:32). In a sense, that His coming is certain, but regarding the time (time) is not known by anyone except the Father in heaven. An understanding of the events that will occur (eschatological) is something that every church of God needs to understand and understand, so that eschatology is not a confusing thing but can build congregational behavior and faith growth, especially for the congregation at GKLI Sihabonghabong. The influence of this understanding will be examined using qualitative descriptive-analysis methods to see to what extent this eschatological understanding affects the behavior of the congregation and the growth of faith in the GKLI Sihabonghabong congregation.